Propuesta de un plan financiero para Optimizar la Liquidez de la constructora grupo las Palmeras E.I.R.L. distrito de Tarapoto, periodo 2013 - Blas Cornelio, Ricardo Breyner (2014)
Globally, the construction industry is very important in the development of a country as it provides basic elements of well-being in a society, it is an activity consisting of a set of procedures undertaken for lifting various types of structures. Perform diagnostics and financial plans are fundamental to study the financial health of the construction companies. Every business must constantly be evaluated to see the possible scenarios to avoid surprises in its development. One of these scenarios is related to the liquidity of the business. Financial Planning is the projection of sales, income and assets, based on alternative production and marketing strategies and determining the resources needed to achieve these projections. For these reasons it appears that company’s civil construction area should practice sound financial management in order to constantly evaluate their results and make the necessary corrections to endure over time and globalized markets looking for quality and innovation. Locally, the research was conducted in the construction company GRUPO LAS PALMERAS EIRL identified with RUC. No. 20450312259, based in Jiménez Pimentel Jr. # 729 - Tarapoto; is a company dedicated to the construction of complete buildings, sale of aggregates and other materials, With 3 years’ experience. In this sense, this research is aimed at developing the financial analysis of the Construction company GRUPO LAS PALMERAS E.I.R.L. also requires the preparation of a financial plan, to guide the proper use of resources.